Involvement of CYP3A4/5 and CYP2D6 in the metabolism of aconitine using human liver microsomes and recombinant CYP450 enzymes - Lan Tang; Ling Ye; Chang Lv; Zhijie Zheng; Yun Gong; Zhongqiu Liu
Aconitine (AC), a famous major Aconitum alkaloid, has effective antirheumatic function with high toxicity. The aim of our study was to in-depth investigate cytochrome P450 isozymes (CYPs)involved in aconitine metabolism in vitro.We used human liver microsomes (HLMs)as well as recombinant CYPs to investigate the metabolism pathways of aconitine by liquid chromatography-tandem mass spectrometry. Fluvoxamine maleate, gemfibrozil, amiodarone hydrochloride, omeprazole, quinidine, diethyldithiocarbamic acid and ketoconazole were successfully applied as test inhibitors for CYP1A2, CYP2C8, CYP2C9, CYP2C19*1, CYP2D6*1, CYP2E1 and CYP3A4/5 in HLMs, respectively. Six CYP-mediated metabolites were found and characterized in human liver microsomes and eight recombinant CYP isoforms. The inhibitor of CYP 3A had a strong inhibitory effect, the inhibitors of CYP 2C9, 2C8 and CYP2D6 had little inhibitory effects, whereas CYP2C19, 1A2 and 2E1 had no obvious inhibitory effects on AC metabolism. Hydroxylation and di-demethylation of aconitine were conducted by human recombinant CYP 3A5 and 2D6, dehydrogenation was only processed by CYP3A4/5, and the main CYP isoforms metabolizing aconitine to demethyl-aconitine and N-deethyl-aconitine were CYP3A4/5 and CYP2D6. In conclusion, aconitine can be transformed into at least six CYP-mediated metabolites in HLMs, CYP 3A4/5 and 2D6 were the most important CYP isoforms responsible for the de-methylation, N-deethylation, dehydrogenation, and hydroxylation of aconitine.
Keywords: ACONITINE; CYTOCHROME P450; METABOLISM; MICROSOMES; LC-MS/MS